Evaluation of stability and yield potential of upland rice genotypes in North and Northeast Thailand - Wasan Jaruchai; Tidarat Monkham; Sompong Chankaew; Bhalang Suriharn; Jirawat Sanitchon (Journal of Integrative Agriculture, 2018)
The planting of upland rice is one cropping option in area with limited water availability and low soil fertility in North and Northeast Thailand. The varietal selection was determined by grain yield potential, wide adaptation, and good stability. This study was aimed at evaluation of indigenous upland rice germplasm for yield and yield stability in multi-locations. Thirty-six upland rice genotypes collected from six provinces of the North and Northeast Thailand and one check variety (Sewmaejan) were assessed under five locations in the rainy seasons of 2009 and 2010. The experiment was laid out in a randomized complete block design with three replications. The genotype grain yield was highly affected by location (59.90%), followed by genotypes (G)×location (L) interaction (12.80%) and genotype (6.79%). The most suitable location for the genotype evaluation was L3 (Khon Kaen-KKU10) which associated with stability of grain yield for all genotypes. Furthermore, biplot and regression analysis indicated that genotype numbers 6 (Jaowmong 1), 10 (Neawmong 1), 18 (Neawdum 1), 19 (Leamna), 20 (Prayaleamkang), 32 (Kunwang 2), and 33 (Kunwang 3) showed great yield stability over five locations. The genotypes will be applicant for upland rice production area and parental base in breeding program.